2017
DOI: 10.1002/ccd.27340
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement for stenotic bicuspid aortic valves: Systematic review and meta analyses of observational studies

Abstract: This analysis suggests that TAVR for BcAV is not associated with excess mortality. The incidence of paravalvular leaks and pacemaker implant is increased compared to tricuspid aortic valve cohorts undergoing TAVR, and operators should weigh these potential complications against the clinical benefit provided by TAVR for BcAV patients at high risk for surgical valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 44 publications
3
25
2
Order By: Relevance
“…Other possible hypotheses include asymmetrical leaflet calcification and resistance to valve expansion . BAV is known to be associated with higher rates of pacemaker implantation in BAV cohorts compared with TAV cohorts . However, we found no difference in pacemaker implantation in the BAV group when directly compared with the TAV group from the same cohort.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Other possible hypotheses include asymmetrical leaflet calcification and resistance to valve expansion . BAV is known to be associated with higher rates of pacemaker implantation in BAV cohorts compared with TAV cohorts . However, we found no difference in pacemaker implantation in the BAV group when directly compared with the TAV group from the same cohort.…”
Section: Discussioncontrasting
confidence: 63%
“…BAV was believed to be more elliptical and would not fit well with prostheses, but a recent study has found that BAV is actually not more elliptical than TAV and should be able to fit commercially available prostheses . Other possible hypotheses include asymmetrical leaflet calcification and resistance to valve expansion . BAV is known to be associated with higher rates of pacemaker implantation in BAV cohorts compared with TAV cohorts .…”
Section: Discussionmentioning
confidence: 99%
“…Considering this with his other aforementioned comorbidities, we favored TAVR as a minimally invasive procedure. Regarding valve selection, a recent meta‐analyses by Reddy et al revealed no significant difference between self‐expanding and balloon‐expanding prostheses regarding acceptable device success rates and low early safety event rates. With the typical oval‐shaped bicuspid anatomy (Sievers I), we decided to work with a self‐expanding valve, which enables adequate sealing due to its conforming frame.…”
Section: Discussionmentioning
confidence: 99%
“…TAVR in bicuspid aortic valve (BAV) has been associated with an increased incidence of paravalvular leak and need for pacemaker implantation . Overall, BAV anatomically is known to have larger SoVs than trileaflet aortic valve.…”
Section: Bicuspid Versus Trileaflet Thrombosis In Tavrmentioning
confidence: 99%